Cd(II) enantiomers embedding helices from 3D frameworks to 2D layers controlled by shapes of ancillary ligands. Issue 7 (30th April 2021) - Xu, Zhong-Xuan; Bai, Xu-Ling; Li, Li-Feng; XU, Shi-Fei
Abstract: Two pairs of chiral coordination polymers, [Cd2 (( R )-CBA)2 (1, 4-BMIB)]n (1- R ), [Cd2 (( R )-CBA)2 (1, 4-BMIB)]n (1- S ), [Cd(( R )-CBA)(1, 3-BMIB)]·H2 On (2- R ), and [Cd(( R )-CBA)(1, 3-BMIB)]·H2 On (2- S ) (H2 CBA = 4-(1-carboxyethoxy) benzoic acid, 1, 4-BMIB = 1, 4-bis(2-methyl-1H-imidazol-1-yl)benzene, 1, 3-BMIB = 1, 3-bis(2-methyl-1H-imidazol-1-yl)benzene), were constructed from lactate derivatives H2 CBA and imidazole ancillary ligands under hydrothermal conditions. These complexes show different structures depending on shapes of ancillary ligands. For the linear 1, 4-BMIB, complexes 1- R and 1- S are three dimensional (3D) frameworks with dinuclear clusters of Cd(II). For the V-shaped 1, 3-BMIB, complexes 2- R and 2- S are two dimensional (2D) layers, where 4-connected Cd(II) centers were isolated by imidazole groups and carboxylic groups from 1, 3-BMIB and H2 CBA, respectively. The resulting complexes were characterized by PXRD, TGA, UV-visible absorptions and CD measurements. Additionally, 1 and 2 exhibit different photoluminescence behavior in the solid state compared to free H2 CBA. Graphical Abstract: